1987
DOI: 10.1080/00288233.1987.10417956
|View full text |Cite
|
Sign up to set email alerts
|

The pH and display life of chilled lamb after prolonged storage under vacuum or under CO2

Abstract: Muscle tissue pH of lamb packaged either under vacuum or in a COz atmosphere rose during prolonged storage at chiller temperatures. Hedonic assessments of meat colour at pack opening did not change significantly during prolonged storage, but the colour stability of displayed meat declined with prolonged storage in a manner that suggests a possible relationship with the observed pH increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 5 publications
3
8
0
Order By: Relevance
“…The changes in the pH of roebuck meat packaged under vacuum and a MA with 40% CO 2 , aged for 7 days, resulted from the process of meat autolysis (Moore and Gill 1987). In meat samples stored in a MA containing 60% CO 2 , the effect of autolytic changes on meat acidity was probably neutralised by high CO 2 concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…The changes in the pH of roebuck meat packaged under vacuum and a MA with 40% CO 2 , aged for 7 days, resulted from the process of meat autolysis (Moore and Gill 1987). In meat samples stored in a MA containing 60% CO 2 , the effect of autolytic changes on meat acidity was probably neutralised by high CO 2 concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, Kim et al (2012) and Rosenvold and Wiklund (2011) studied the changes in quality of vacuum-aged lamb during further display as affected by several processing conditions, i.e., electrical stimulation, vacuum storage temperatures, atmosphere composition; however, in those studies the quality changes were not compared with non-aged lamb. Moreover, Meat Science 98 (2014) 646-651 Moore and Gill (1987) compared the display life (based on color acceptability) between lamb aged under vacuum and not aged-lamb. They found that vacuum ageing resulted in a reduction of color stability during aerobic display, with the magnitude of this effect depending on both storage time and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant effect of storage time (P < 0.05) because of the high pH value of the chilled 8 weeks' samples. Moore & Gill (1987) noted a marked rise in pH of lamb chops stored under either vacuum or CO 2 , which they attributed to microbial activity. In the present study the pH rise was less consistent, and this lessened response is probably the result of the lower microbial loading one would expect with excised longissimus dorsi muscles as opposed to the whole chop.…”
Section: Resultsmentioning
confidence: 99%
“…Lamb chops packaged in this system had an increase in muscle tissue pH during storage, although the meat still retained some characteristics of fresh meat such as "blooming" in Received 19 October 1988; accepted 24 January 1989 aerobic packaging (Moore & Gill 1987). If such a system could be applied to frozen-thawed lamb cuts without loss of quality, it could indeed be beneficial.…”
Section: Introductionmentioning
confidence: 99%